Conforming and nonconforming personality and stress coping styles in combat athletes - Bernacka, R. A.; Sawicki, B.; Mazurek-Kusiak, A.; Hawlena, J. (Journal of Human Kinetics, 2016)
The main objective of this study was to investigate whether the personality dimension of conformism/nonconformism was a predictor of stress coping styles in athletes training combat sports, and to present the characteristics of this personality dimension in the context of the competitors` adaptive/innovative sport performance. Scores of 346 males practising combat sports such as kick boxing, MMA, thai boxing, boxing and wrestling were analyzed. The participants completed the Creative Behaviour Questionnaire (KANH III) measuring the conformity/nonconformity personality dimension and the Coping Inventory for Stressful Situations (CISS) measuring stress coping styles. The comparative analyses were conducted only for the groups of conformists and nonconformists. Differences in stress coping styles between conformists and nonconformists training combat sports were found as nonconformists tended to prefer the task-oriented coping style. Conclusively, a higher rate of nonconformity was associated with increasingly frequent occurrence of task-oriented coping and decreasingly frequent emotion-oriented coping.